Making the most of the imaging we have: using head MRI to estimate body composition. Issue 4 (April 2016) - Lack, C.M.; Lesser, G.J.; Umesi, U.N.; Bowns, J.; Chen, M.Y.; Case, D.; Hightower, R.C.; Johnson, A.J.
Abstract : Aim: To investigate the use of clinical head magnetic resonance imaging (MRI) in determining body composition and to evaluate how well it correlates with established measures based on abdominal computed tomography (CT). Materials and methods: Ninety-nine consecutive patients were identified who had undergone both brain MRI and abdominal CT within a 2-week span. Volumes of fat and muscle in the extracranial head were measured utilising several techniques by both abdominal CT and head MRI. Results: MRI-based total fat volumes in the head correlated with CT-based measurements of fat in the abdomen using both single-section ( r =0.64, p <0.01) and multisection ( r =0.60, p <0.01) techniques. No significant correlation was found between muscle volumes in the abdomen and head. Conclusion: Based on the present results, head MRI-based measures may provide a useful surrogate for CT measurements of abdominal fat, particularly in patients with neurological cancers, as head MRI (and not abdominal CT) is routinely and repeatedly obtained for the purpose of clinical care for these patients. Highlights: We compared body composition using brain MRI with previously proven abdominal CT. Fat and muscle volumes of the extracranial compartment can be measured by MRI. Muscle volume in the face does not correlate with abdominal muscle volume. Fat volume in the face can be used as a surrogate for abdominal fat volume.